Secrets of spiritual stamina - Briscoe, D. Stuart ([Minneapolis, Minn.] : Billy Graham Evangelistic Association, 1994)
Healthy habits for lasting faith.
Originally published: Wheaton, Ill. : H. Shaw, 1994.
Keywords: Christian life; Bible. -- Study and teaching